2016
DOI: 10.1038/srep34378
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Main and Interaction Effects on Cu(II) and Cr(VI) Decontamination by Nitrogen–Doped Magnetic Graphene Oxide

Abstract: A nitrogen–doped magnetic graphene oxide (NMGO) was synthesized and applied as an adsorbent to remove Cu(II) and Cr(VI) ions from aqueous solutions. The individual and combined effects of various factors (A: pH, B: temperature, C: initial concentration of metal ions, D: CaCl2, and E: humic acid [HA]) on the adsorption were analyzed by a 25−1 fractional factorial design (FFD). The results from this study indicated that the NMGO had higher adsorption capacities for Cu(II) ions than for Cr(VI) ions under most con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 52 publications
5
31
0
Order By: Relevance
“…It was known that HA contains a lot of functional groups such as phenolic hydroxyls, carboxyl, amidogen and double bonds, which can form negative charges bound by dissociating of groups . Thus, these negative groups might combine with TC and DC and form soluble TC–HA and DC–HA complexes to reduce the adsorption capacity , , . Moreover, aromatic backbones of HA induced static repulsion as reported in a previous study .…”
Section: Resultsmentioning
confidence: 77%
“…It was known that HA contains a lot of functional groups such as phenolic hydroxyls, carboxyl, amidogen and double bonds, which can form negative charges bound by dissociating of groups . Thus, these negative groups might combine with TC and DC and form soluble TC–HA and DC–HA complexes to reduce the adsorption capacity , , . Moreover, aromatic backbones of HA induced static repulsion as reported in a previous study .…”
Section: Resultsmentioning
confidence: 77%
“…Recently, there have been various reports on the utilisation of BC for wastewater treatment and remediation of contaminated soil, owing to its cost‐effectiveness for the removal of chemical contaminants, namely, heavy metals and organic contaminants . There have also been several interesting proposals for the use of BC as a stabiliser of nano‐sized metal oxides which tend to aggregate because of their high surface energy and strong magnetic attraction, leading to reduced effective surface area and contact area when used for the removal of pollutants . For instance, Jung et al .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8] There have also been several interesting proposals for the use of BC as a stabiliser of nano-sized metal oxides which tend to aggregate because of their high surface energy and strong magnetic attraction, leading to reduced effective surface area and contact area when used for the removal of pollutants. [9][10][11][12][13][14] For instance, Jung et al explored combined electrochemical modifications for the fabrication of a MgO/biochar composite which exhibited excellent aqueous phosphate adsorption properties represented by a Langmuir-Freundlich maximum adsorption capacity of 620 mg-P g -1 . 15 Zhang et al synthesised a magnetic BC material through thermal pyrolysis and demonstrated that the material is an excellent sorbent for the removal of arsenic (V) from an aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several decades, many advanced technologies have been used in wastewater treatment, such as adsorption, coprecipitation and membrane filtration . The membrane filtration process gained its popularity for its low‐energy requirement, high separation efficiency, no phase changing, device simplicity, and environmental friendly properties .…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several decades, many advanced technologies have been used in wastewater treatment, such as adsorption, coprecipitation and membrane filtration. [1][2][3][4] The membrane filtration process gained its popularity for its low-energy requirement, high separation efficiency, no phase changing, device simplicity, and environmental friendly properties. 5,6 Although membrane bioreactors (MBRs) and other filtration processes, such as reverse osmosis (RO), nanofiltration (NF) and ultrafiltration (UF), have been in commercial use for several decades, [5][6][7][8] membrane biofouling still remains an intractable problem that limits their development.…”
Section: Introductionmentioning
confidence: 99%